Enhanced properties of high-silica rice husk ash-based geopolymer paste by incorporating basalt fibers. (10th June 2020) - Saloni,; Parveen,; Pham, Thong M.
Highlights: Basalt fiber enhanced the strength characteristics of the geopolymer composites. Setting times of RHA based geopolymer were found to increase with increase of basalt fiber content. Reduced drying shrinkage was obtained for RHA based geopolymer paste with basalt fiber. The microstructure and properties of the RHA and basalt fiber based paste has been studied. Homogeneous and denser paste may be developed by using basalt fiber and RHA. Abstract: In this study, the effect of different basalt fiber contents (0%, 10%, 20%, 30%, 100% by binder mass) as a replacement of rice husk ash on the fresh, hardened and microstructural properties of geopolymer paste has been evaluated. NaOH (12 Molar) and Na2 SiO3 were used to produce geopolymers. Different characteristics, i.e. initial setting and final setting times, bulk density, porosity, compressive and flexural strengths were investigated by using various techniques, such as scanning electron microscopy, X-ray diffraction and energy dispersive spectroscopy. Results showed that basalt fibers exhibited positive effects on the fiber-matrix transition zone as increased initial setting time, final setting time, bulk density and compressive and flexural strengths with the increased basalt fiber contents. Meanwhile, chemical analysis showed that basalt fibers acted as reinforcements and thus improved the characteristic of geopolymer paste. The major crystalline phases presented in the resultant geopolymer were quartz, calcium silicate hydrate and magnesioferrite. In addition, reduced values of critical pore size and total porosity were observed with an increase of replacement content in rice husk ash. The results of the present study support basalt fibers and rice husk ash as promising solid waste materials for use in the production of geopolymers.